Tipologi dan Dinamika Wilayah Pesisir Padangbai di Kabupaten Karangasem - Wedanta Pucangan, I Putu Wahyu; Prajnawrdhi, Tri Anggraini; Paramadhyaksa, I Nyoman Widya (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 10 No 2 (2023): October 2023, 2023)
This study examines typologies and dynamics, disaster potential and development schemes for the Padangbai coastal area. Analysis within is based on primary and secondary spatial typologies. The results of the literary synthesis show that there is a link between coastal typologies and coastal dynamics, which are inseparable from potential disasters and coastal development. This study uses a qualitative method of descriptive analysis of both secondary data and data collected from field observations. The development of typologies for the Padangbai coastal area is divided into three stages. The first is the establishment of a man-made coastal typology. The second is the formation of beaches on cliffs due to erosion by sea waves. The third is the formation by sedimentation processes on the coast, namely sea deposition beaches. Coastal dynamics that occur in the Padangbai Coastal Area consist of two processes, namely anthropodynamics and hydrodynamics. Based on the typology of the wave erosion coast, potential forms of development for the Padangbai Coastal Area are accommodation for tourism, snorkelling, diving and water sports with a low level of disaster potential. The potential for development in the Padangbai Coastal Area based on the coastal typology of the marine deposition coast is the development of marine infrastructure (harbour) and tourism accommodation with high to low levels of disaster potential. Keywords: coastal; typology; dynamics; disaster Abstrak Penelitian ini mengkaji tipologi pesisir, dinamika pesisir, potensi bencana dan pengembangan pesisir di Wilayah Pesisir Padangbai. Analisisnya didasarkan pada tipologi keruangan primer dan sekunder. Hasil sintesa literatur didapat bahwa ada kaitan antara tipologi dan dinamika pesisir yang tidak terpisahkan dari potensi bencana serta pengembangannya. Penelitian ini menggunakan metode kualitatif terdiri dari deskriptif dari data yang diperoleh dari data sekunder dan observasi lapangan. Pembentukan tipologi di Wilayah Pesisir Padangbai dapat dibagi menjadi tiga tahapan. Pertama adalah pembentukan tipologi pesisir buatan manusia. Kedua pembentukan w ave e rotion c oast pada cliff , dan ketiga pembentukan oleh proses sedimentasi di pesisir yaitu marine deposition coast . Dinamika kepesisiran yang terjadi di Wilayah Pesisir Padangbai terdiri dari dua proses yaitu antropodinamik dan hidrodinamik. Potensi pengembangan di Wilayah Pesisir Padangbai berdasarkan tipologi pesisir wave erotion coast adalah akomodasi pariwisata, snorkeling, menyelam dan olahraga air dengan potensi bencana rendah. Potensi pengembangan di Wilayah Pesisir Padangbai berdasarkan tipologi pesisir m arine d eposition c oast adalah pembangunan infrastruktur laut (pelabuhan) dan akomodasi pariwisata dengan potensi bencana tinggi-rendah. Kata kunci: pesisir; tipologi; dinamika; bencana